Ductal Carcinoma In Situ: What Can We Learn from Clinical Trials?. (9th May 2012) - Fortunato, Lucio; Poccia, Igor; de Paula, Ugo; Santini, Elena
Abstract : Ductal Carcinoma in situ has been diagnosed more frequently in the last few years and now accounts for approximately one-fourth of all treated breast cancers. Traditionally, this disease has been treated with total mastectomy, but conservative surgery has become increasingly used in the absence of unfavourable clinical conditions, if a negative excision margin can be achieved. It is controversial whether subgroups of patients with favourable in situ tumors could be managed by conservative surgery alone, without radiation. As the disease is diagnosed more frequently in younger patients, these issues are very relevant, and much research has focused on this topic in the last two decades. We reviewed randomized trials regarding adjuvant radiation after breast-conservative surgery and compared data with available retrospective studies.